Model dziennikarstwa zorientowany na obywateli w perspektywie paradygmatu społecznej odpowiedzialności mediów. Przykład prasy w Polsce - Secler, Bartłomiej; Stępińska, Agnieszka; Jurga-Wosik, Ewa; Narożna, Dominika; Adamczewska, Kinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This paper aims to present a theoretically-empirical reflection on the citizen-oriented model of journalism developed from the social responsibility of the media paradigm. The main indicator of that model is the significant attention paid by journalists to the current perspective of the citizens (in terms of their expectations, demands, actions), to educate citizens about their rights and obligations, as well as to encourage people to actively participate in public debate. The study was conducted under the framework of the international comparative project “Journalistic Role Performance Around the Globe”, launched and coordinated by C. Mellado and L. Hellmueller from Texas State University, USA (www.journalisticperformance.org). The results of empirical research (an analysis of the contents of four Polish daily newspapers) revealed that Polish journalism insufficiently incorporates the model of civic service, one of whose most rudimentary aims is the support, education and representation of the citizens’ interests.